Children's places : cross-cultural perspectives - Olwig, Karen Fog, 1948-; Gulløv, Eva (Routledge, 2003)
Children's Places examines the ways in which children and adults, from their different vantage-points in society, negotiate the 'proper place' of children in both social and spatial terms. It looks at some of the recognised constructions of children, including perspectives from cultures that do not distinguish children as a distinct category of people, as well as examining contexts for them, from schools and kindergartens to inner cities and war-zones. The result is a much-needed insight into the notions of inclusion and exclusion, the placement and displacement of children within ge.